TED Talksトップ30のトピックと言語的特徴 - Shiomi Kayoko (MEDIA, ENGLISH AND COMMUNICATION, 2021)
TED with the aim of "Ideas worth spreading" has published more than 3,600 talks on their website. In this article, the author examined the 30 most viewed TED Talks and analyzed the topics and linguistic features of introductory and concluding sections. The analysis has found that among the topics, those that deal with social issues and the humanities are mainly selected. As for the linguistic features of these TED Talks, speakers use a variety of techniques to draw participants' interest to their topics, including questions to the participants and personal stories related to the topics. With regards to the endings, speakers use more open-ended questions and rhetorical questions. They also often switch from the use of the subject "I" to "we" in the final messages to appeal to the audiences. The analysis of these TED Talks should provide practical insights into possible ways to make intriguing and inspiring presentations. 「広める価値のあるアイデア」の理念の基、TED Talks ではこれまでに 3,600 以上のトークを配信している。それぞれの分野で活躍しているスピーカーが、様々なアイデアや取り組みを世界に向けて発信し、動画は世界中で視聴されている。本稿ではこれらの TED Talksの中から視聴回数が最も多いトップ 30 のトークを選び、話されているトピックを調べた。また、話の導入部分と最後のメッセージを伝える部分を中心に、スピーカーが人々を惹きつけ、聞き手の印象に残るプレゼンテーションを行うためにどのような工夫をしているか、言語的特徴を中心に分析した。その結果、導入部分では前置き表現を含め、スピーカーが自分の経験を語り自己開示を行ったり、テーマに関連のある質問を投げかけて参加者と何らかのつながりを持とうとしたりしていることが分かった。また、最後の部分では、スピーカーは主なメッセージを聞き手にも当事者として考えてもらうため、主語を I から we に変えて提案を行ったり、行動をとる必要性を反復表現で述べたり、アドバイスを端的に命令形で伝えたり、小さな変化が大きな変革を起こす可能性を、仮定法や強調構文を用いるなどして工夫していた。